Officially social: Developing a social media crisis communication strategy for USGS Volcanoes during the 2018 Kīlauea eruption - Stovall, Wendy K.; Ball, Jessica L.; Westby, Elizabeth G.; Poland, Michael P.; Wilkins, Aleeza; Mulliken, Katherine M. (Frontiers in Communication, 2023)
The USGS Volcano Science Center has a long history of science and crisis communication about volcanoes and their eruptions. Centered mainly on websites, email notifications, traditional media, and in-person interaction in the past, our toolkit has expanded in the last decade to include social media channels. This medium has allowed us to communicate with both long-standing and new audiences in new ways. In the process, social media communication has further developed trust in USGS researchers. In particular, the nearly 4-month-long 2018 eruption of Kīlauea volcano in the State of Hawaii necessitated the rapid development of a communication strategy that more deeply incorporated web and social media (Facebook, Twitter) channels to share critical eruption information. This was the first major volcanic eruption response where the USGS used official social media accounts as a significant form of public communication and outreach. These timely and conversive interactions furthered engagement with residents and reinforced the USGS as an authoritative and approachable voice on the eruption with U.S. and international audiences. In many cases, USGS Volcanoes’ social media channels were also sampled directly by media outlets looking to provide current information, particularly by local reporters and citizen journalists. This helped disseminate scientific information directly to those who needed it and removed pressure from observatory scientists to respond to media requests. In short, the conversational tone and engaged and inquisitive online audience allowed the USGS Volcanoes’ social media channels to act as a virtual community meeting, which nurtured a nearly continuous educational environment for both directly affected and distant members of the public. We present the history and details of this strategy here in hopes that it will benefit volcano observatories and other official agencies and crisis communicators.